60th birthday of Yurij Holovatch - C. von Ferber (Condensed Matter Physics, 2017)
On June 16th 2017, Dr. Sci., Professor Yurij Holovatch, Head of the Laboratory for Statistical Physics of Complex Systems, Corresponding Member of the National Academy of Sciences of Ukraine, full member of the Shevchenko Scientific Society, member of the Editorial Board of “Condensed Matter Physics”, celebrates his 60th birthday.